Elaboración de un manual infográfico de los animales domésticos para la facultad de medicina veterinaria de la Universidad Técnica De Cotopaxi. - Martinez Toapanta, Edwin Fernando (2013)
The thesis deals with the graphic design of an infographic manual containing knowledge basic about the morphological characteristics and habitat of domestic animals a study in the veterinary degree of the Technical University of Cotopaxi, in Ecuador, with the use of programs and software, becoming educational resources, mediates communication, supported by theoretical considerations about the characteristics acquired by graphic design and infographics as a result of development of Information and Communication Technologies. Quantitative and qualitative research assumptions are assumed, privileging the second. The use of technological, graphic design, theoretical, empirical methods and mathematical statistics allowed to assess the feasibility of graphic design computerized, as well as, in the application in the construction of the infographic manual referred to pets based on criteria of users of the race of Veterinary at the University of Granma, Cuba. The acceptance of computerized graphic design is announced, from the layout, specification and visualization in the infographic manual.